PENGEMBANGAN MEDIA AUDIO VISUAL MATA KULIAH MULTIMEDIA PEMBELAJARAN TEKNOLOGI PENDIDIKAN FIP UNM - Taufik, Ilham; Nurhikmah H.; Pattaufi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The problem in this study is that the learning media used is less innovative and the need for media that can increase students' learning motivation. The purpose of this study was to measure the need for audio-visual media for the Multimedia Learning course in the Educational Technology Study Program, FIP UNM, to design audio-visual media for the Multimedia Learning course that will be developed, and to measure the validity and practicality of the audio-visual media for the Multimedia Learning course that was developed. The approach used in this study is the development of 4D (Four D Models) which is limited to 3D. The study was conducted in the Educational Technology Study Program, the subjects in the study were 30 Educational Technology students, 1 lecturer in charge of the course and 2 validators. The results of the study showed that the results obtained from the identification of the level of student needs were in the very needed qualification. The results obtained from the validation of material/content experts were in the very valid qualification and the validation of media experts were in the valid qualification. To test the level of practicality of the product, small group trials, large group trials and responses from lecturers were carried out. From the three trials, the results obtained were good qualifications and suitable for use.